Editorial - Crozier, Gill (International Journal about Parents in Education, 2023)
The articles for this special issue of IJPE arose out of the 11th biennial conference of the European Research Network About Parents in Education (ERNAPE) which was held in July 2017 at the University of Roehampton, London, UK. The conference theme was Intensification, constraint and opportunity: changing roles for parents, schools and communities. Addressing equity and diversity issues. The conference attracted participants from across the world and this global dimension of ERNAPE is also indicated by the composition of the articles presented here. The ten articles that comprise the special issue are based on research arising in Canada, Taiwan, China, Switzerland, Poland, Indonesia, the UK, Cyprus, Finland and Russia. This diverse representationindicates the growing and widespread international research and policy concerns and significance of parents, communities and education.